ArcData : citizen science - Guðmundur Sverrisson 1973-; Tryggvi Dalmann Ólason 1990- (2021)
Citizen Science is a prototype of an app that was designed and created for ArcData ehf, as a final project towards BSc degree in Computer science at Reykjavík University. The app enables users to contribute information about the environment around them. The information will be stored in a database that can be used for scientific research.